KV11.1 Potassium Channel and the Na+/H+ Antiporter NHE1 Modulate Adhesion-Dependent Intracellular pH in Colorectal Cancer Cells - Iorio, Jessica; Duranti, Claudia; Lottini, Tiziano; Lastraioli, Elena; Bagni, Giacomo; Becchetti, Andrea; Arcangeli, Annarosa (Frontiers in Pharmacology, 2020)
Increasing evidence indicates that ion channels and transporters cooperate in regulating different aspects of tumor pathophysiology. In cancer cells, H+/HCO3- transporters usually invert the transmembrane pH gradient typically observed in non-neoplastic cells, which is thought to contribute to cancer malignancy. To what extent the pH-regulating transporters are functionally linked to K+ channels, which are central regulators of cell membrane potential (Vm), is unclear. We thus investigated in colorectal cancer cells the implication of the pH-regulating transporters and KV11.1 (also known as hERG1) in the pH modifications stimulated by integrin-dependent cell adhesion. Colorectal cancer cell lines (HCT 116 and HT 29) were seeded onto 1 integrin-dependent substrates, collagen I and fibronectin. This led to a transient cytoplasmic alkalinization, which peaked at 90 minutes of incubation, lasted approximately 180 min, and was inhibited by antibodies blocking the 1 integrin. The effect was sensitive to amiloride (10 µM) and cariporide (5 µM), suggesting that it was mainly caused by the activity of the Na+/H+ antiporter NHE1. Blocking KV11.1 with E4031 shows that channel activity contributed to modulate the 1 integrin-dependent pHi increase. Interestingly, both NHE1 and KV11.1 modulated the colorectal cancer cell motility triggered by 1 integrin-dependent adhesion. Finally, the 1 integrin subunit, KV11.1 and NHE1 co-immunoprecipitated in colorectal cancer cells seeded onto Collagen I, suggesting the formation of a macromolecular complex following integrin-mediated adhesion. We conclude that the interaction between KV11.1, NHE1 and β1 integrin contribute to regulate colorectal cancer intracellular pH in relation to the tumor microenvironment, suggesting novel pharmacological targets to counteract pro-invasive and, hence, pro-metastatic behavior in colorectal cancer.